747 THE DIAGNOSIS AND MANAGEMENT OF HYPERKALAEMIA IN MEDICAL AND ELDERLY CARE INPATIENTS AT A DISTRICT GENERAL HOSPITAL. (8th March 2022) - Broadhurst, C; Thompson, K; Tan, W
Abstract: Introduction: Severe hyperkalaemia is a dangerous and potentially life-threatening condition. Despite this knowledge, the incidence of hyperkalaemia in hospital inpatients remains high. On review of the acute management of hyperkalaemia at Croydon University Hospital, only 50% of medical and elderly care inpatients were managed correctly in line with hospital guidelines, and 50% of surveyed doctors did not feel confident managing acute hyperkalaemia—highlighting an urgent requirement for improvement. The project objectives were to improve management in line with hospital guidelines, overall prescription accuracy and the confidence of junior doctors in managing acute hyperkalaemia. Methods: Two PDSA cycles; cycle one involved teaching sessions to doctors and the creation and circulation of information posters. Cycle two involved the development and implementation of a new electronic order prescription set for the management of acute hyperkalaemia. Results: Post-intervention results showed an improvement in the correct management of hyperkalaemia from 50% to 80%. Prescription accuracy improved from 90% to 100%. Doctors reported an improvement in their overall confidence from 50% to 64%. Sub-group analysis identified no post-intervention improvement in the correct management of hyperkalaemia in care of the elderly (COTE, >80 years) patients. COTE patients were also less likely to be managed correctly (45% vs 57%) and to have accurate prescriptions (71% vs 100%). However, prescription accuracy did improve in the COTE group (50% to 100%). Conclusion: This project achieved its initial objectives. However, COTE patients were less likely to be managed correctly. This may be secondary to being more complex patients, having multiple co-morbidities or significant polypharmacy, which may further contribute to hyperkalaemia. Doctors may feel less confident suspending or modifying medications in these cases and seek input from specialist teams prior to doing so. Future interventions will focus on delivering teaching sessions on hyperkalaemia in complex cases to improve confidence and understanding.